The place and role of purgatory in the twenty-first century: a visual content analysis of students’ AI-generated works - Cirklová, Jitka (Theology, 2024)
This article examines current perceptions of purgatory among young people and its role in society. Architecture students’ visual material explores the evolving concept of purgatory and its importance today. The study analyses how ideas of purification and hybridity are understood in contemporary secular society. Using a structured visual research framework, the study incorporates participatory seminars, art-based methodologies and innovative AI techniques. It investigates young people’s views on purgatory and their understanding of the cosmos, considering contemporary interpretations and the concept of presentism. By combining creative and conventional research approaches, this text aims to enhance understanding and generate new insights. The analysis uncovers how purgatory and transitional spaces are understood in today’s society, revealing individual interpretations of religious teachings. It also highlights the importance of creative research methods in understanding complex religious ideas.